The External Cruising Costs of Parking - Eren Inci; Jos N. van Ommeren; Martijn Kobus (Tinbergen Institute, 2015)
Existing work emphasizes the importance of traffic congestion externalities, but typically ignores cruising-for-parking externalities. We introduce a novel methodology to estimate the marginal external cruising costs of parking. The level of cruising is identified by examining to what extent the car inflow rate into the parking location falls with parking occupancy level. For a commercial street in Istanbul, we demonstrate that a marginal car parking for one hour induces 3.6 other cars to cruise for parking. This translates into an external cruising cost that far exceeds the external traffic congestion cost created by the trip.
Keywords: D62; H23; L91; R41; R48; 330; administrative parking data; cruising for parking; external costs of parking; parking fee; parking occupancy rate